The Impact of the Covid-19 Pandemic on the Increase in Insurance Claims in Indonesia: An Empirical Study on BPJS Employment - Rheny Windi Nabila; Zayyan Tsabitah Panjaitan; Fikri Maulana Matullesy; Aldris Mulya Putra; Manswab Mahsen Abdulrahman (ISNU Sumatera Utara, 2025)
The Covid-19 pandemic has caused multidimensional pressure on the employment social security system in Indonesia, especially on the increase in claims for BPJS Employment benefits. The surge in Covid-19 cases has a direct impact on the increase in the number of layoffs, the decrease in worker income, and the increased risk of health and death. This condition encourages participants to disburse social security benefits to meet basic living needs. This study aims to analyze the impact of the Covid-19 pandemic on the increase in insurance claims at BPJS Ketenagakerjaan and its implications for the sustainability of social security fund management. The research method used is normative juridical with a legislative and conceptual approach, supported by secondary data in the form of official documents, annual reports, and scientific literature related to employment social security. The results of the study show that at the beginning of the pandemic, Old Age Security (JHT) and Pension Security (JP) claims experienced a significant increase due to mass layoffs. Furthermore, in 2021, claims for Death Insurance (JKM) and Work Accident Insurance (JKK) also increased in line with the high mortality rate and occupational risk. This study concludes that BPJS Ketenagakerjaan needs to strengthen the readiness of liquid funds and develop a digital service system to face similar crises in the future and ensure the sustainability of social protection for workers.